The Strategic Task Overload Model: History, Status, Challenges, and Extensions into New Domains. (September 2017) - Sebok, Angelia
In this symposium we present the history, current status and challenges of the Strategic Task Overload Management (STOM) model of task switching, positing that parameters of priority, interest difficulty, salience and time-on-task are the factors that drive switching. We present four papers examining extensions of the model. In the first presentation, Wickens & Gutzwiller describe in detail the nature and background of the five parameters and their roots in models of scanning. In the second presentation, Gutzwiller & Sitzman consider the effects of multitasking and priority on task selection. Then Gilbert & Wickens show the extension of STOM to business tasks by presenting results of an experiment that systematically evaluate the role of task priority and goal setting. In the final presentation, Barg-Walkow & Rogers demonstrate the relevance of STOM to vitally important task management in the emergency room.